ENT 530 Social media portfolio: Adapter 2 in 1 Lightning / Luqman Hakim Norazmi - Norazmi, Luqman Hakim (2021)
Gaming Gadget Shop conducts an online business based on Facebook. It is a sole proprietorship business which is owned by Luqman Hakim Bin Norazmi. The location of the business is at Lot 135 Kg Dewan Beta, 15100 Kota Bharu Kelantan. This location is very strategic because it is near to town where everything is accessible including to post the parcel and can cash on delivery with customers. The expectation of the establishment of this business is to help customer who cannot use charging cable and earphone at the same time on their iPhone 7 and above. We plan to build a strong market position and wish to expand our business, making Gaming Gadget Shop known to people all over Malaysia. One of the reasons the business chooses online shopping because it is very convenient not only for the seller but also for the customers. Internet can change the way consumers shop to buy goods and services as it has rapidly evolved into a global phenomenon. The business has started using the Internet with the aim of cutting marketing costs, thereby reducing the price of the products and services in order to stay ahead in highly competitive markets. The business also using the Internet to convey, communicate and disseminate information in order to sell the product, to take feedback and also to conduct satisfaction surveys with customers. Customers use the Internet not only to buy the product online, but also to compare prices and product features especially from the feedback and review of other customers